Pengaruh Kualitas Produk, Harga Dan Keamanan Layanan Pelanggan Terhadap Kepuasan Konsumen Di Tik Tok Shop Di Rantauprapat - Risma Afrida Ritonga; Sumitro Sarkum; Elvina Elvina (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Research that aims to determine the effect of product quality, price, and customer service security on customer satisfaction on the Tiktok Shop application in rantauprapat. is the result of quantitative research, which aims to answer questions about the effect of product quality, price, and customer service security on customer satisfaction on the tiktok shop application. the research method I used was quantitative research using the survey method. In sampling using google form or questionnaire with 100 respondents. data collection techniques using a questionnaire processed using SPSS version 23. Data analysis using multiple linear regression. The results showed that product quality (X1) did not have a positive effect on the Consumer Satisfaction variable at tik tok shop. Then the significant value of the t value is 1.532 < t table 1.987, this means that the variable effect of product quality does not have a positive effect on the Consumer Satisfaction variable. Then the significant value is 0.129 < 0.05, which means that the variable effect of product quality is not significant on the Consumer Satisfaction variable, Price (X2) The calculated t value is 4.287> t table 1.987, this means that the price variable has a positive effect on the purchase satisfaction variable. Then the significant value is 0.00 <0.05, which means that the Price variable has a significant effect on the Consumer Satisfaction variable, customer service security (X3) The calculated t value is 2.407> t table 1.987, this means that the service security variable has a positive effect on the Consumer Satisfaction variable. Then the significant value is 0.018 <0.05, which means that the significant variable between security and purchasing decisions on the tik tok shop, has an effect on consumer purchasing decisions in the TikTik Shop application. Research shows that the variables influence product quality, price, security services on customer satisfaction at the Tik Tok shop. Keywords: Product Quality, Price, Security Services, Consumer Satisfaction